SISTEM INFORMASI MANAJEMEN PENJUALAN TOKO MUSONG BERBASIS CODEIGNITER (STUDI KASUS TOKO MUSONG) - Rian Dwi cahyadi; Riki Afriansyah; Irwan Irwan (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Musong is a wholesaler of healthy drinks, especially Bangka wild forest honey located in Bangka Belitung. trading activities are still manual and advertising and promotions are still limited. For that we want a data framework that can develop to promote and cooperate with the exchange of transactions so that it is more effective, fast and simple without being hindered by distance and time. The purpose of this study is to develop a business data framework for a website-based Musong store. Therefore, a CODEIGNITER-BASED MUSONG STORE SYSTEM is planned or known as a Web-based business. This application is designed as simple as possible to make it easier for clients to buy goods at the Musong shop online whenever and wherever without taking up time. The use of the site is relied on to expand the scope of advertising, expand the offering.